Characteristics and Management of Neck and Trochanteric Femur Fractures at a Tertiary Hospital in Indonesia: A Retrospective, Single-Center Study - Ndilalah Pulungan; Yusa Muhammad Thoriq; Felix Giovanni Hartono; Muhammad Luthfi Adnan; Dadang Rona Sasetyo (Journal Orthopaedi and Traumatology Surabaya)
Background: Although hip fractures are common among the elderly population, there are still limited studies on neck-trochanteric fractures, one of the less common types of hip fractures. This study aims to describe the characteristics of patients and their management in patients with neck trochanteric fractures.